ANALYSIS OF CHANGES IN AFRICAN SWINE FEVER VIRUS GENETIC STRUCTURE AND BIOLOGICAL PROPERTIES DURING ADAPTATION TO CONTINUOUS CELL CULTURE - Ali Mazloum; N. G. Zinyakov; A. S. Pershin; I. V. Shevchenko; I. Yu. Zhukov; D. N. Fedoseyeva; D. V. Sharypova; A. S. Igolkin; N. N. Vlasova (Ветеринария сегодня)
Functions of many African swine fever virus genes and multigene family members have not been yet understood. In particular, no virus genes directly associated with pig virulence have been identifed. Identifcation of such genes will enable preparation of deletion mutant ASF virus strains as well as development and testing of pilot safe vaccines based on the said virus strains. Comparative analysis of the virus biological characteristics and detection of diﬀerences in its genome structure aﬀecting certain phenotypic features is a main method used for the virus basic pathogenicity and immunogenicity examination. The most interesting and eﬀective approach to addressing this problem is an analysis of changes in the gene structure during ASF virus adaptation to replication in continuous cell culture. The said factors have made continuous cell culture-adapted variant ASF virus preparation necessary. Variant viruses with modifed biological features were prepared during adaptation of ASFV Odintsovo 02/14 isolate to replication in CV-1 cell culture. Lethality level was 16.7% when pigs were infected with adapted variant virus at 30th passage and survived animals became resistant to reinfection with homologous virulent ASFV Arm07 isolate. It should be noted that the virus passage in non-permissive cell culture up to 30 serial passages did not result in changes in its genotype; however, a large 3,000 bp deletion similar to that one in continuous Vero-cell culture-adapted BA71V strain genome appeared in right terminal variable region of the genome.